Presidential Election 2022: A Euroclash Between a "Liberal" and a "Neo-Nationalist" France Is Coming - Thierry Chopin; Samuel B. H. Faure (Intereconomics, 2021)
The main question surrounding the re-election of Macron is the uncertain balance of France's flexilateral policy vis-à-vis the EU in a post-Brexit and COVID-19 context: Strengthening European integration by changing France's practice towards the EU or taking an inter-governmentalist turn by using – in a very classical way – Europe as an "Archimedes' lever" to defend national interests.
Keywords: 330; Präsidentschaftswahl; Europäische Integration; Frankreich